Selection of potato varieties resistant to wart Synchytrium endobioticum Schilbersky Percival - Zelya, A.; Zelya, G.; Sonetsi, T.; Makar, T. (Quarantine and plant protection, 2022)
Goal. The results of researches for selection potato varieties and breeding material of Ukrainian and foreign selection resistant to wart for inclusion in the State Register of plant varieties suitable for distribution in Ukraine and introduce them into disease foci. Methods.The study involved 13 varieties of potatoes: 3 varieties of Ukrainian selection and 10 — foreign. Evaluation of breeding material for resistance to common 1 (D1) and aggressive pathogens of potato cancer was performed in the laboratory of the Ukrainian Research Plant Quarantine Research Station of the NAAS on an artificial infectious background according to EPPO Standard PM 7/28/1 and EPPO Standard PM 7/28 / 2 and performed in the laboratory of the Ukrainian Research Plant Quarantine Research Station of the NAAS on an «Methods for evaluation and selection of breeding material for potatoes resistant to cancer Synchytrium endobioticum (Schilb.) Perc., Harmonized with EU requirements» and in the field in foci of pathogen spread. Results. As a result of laboratory and field studies on the evaluation and selection of potato varieties resistant to cancer, one variety of potato of Ukrainian selection Medea — selection of the Institute of Potato NAAS and one variety of foreign selection Soraya, selection Norica Nordring-Kartofeltsucht- und Fermerbungs comprehensive resistance to all wart. Of the 13 potato varieties tested, all (100%) were rated resistant to the usual pathotype of the cancer agent; up to 11 (Mizhhirya) and 22 (Bystrets) pathotypes, 6 varieties (46.1%) of resistant varieties were selected; 8 varieties (61.5%) resistant to 13 (Rakhiv) aggressive pathotype were found; to 18 (Yasinya) — 5 varieties of potatoes (38.4%).Three varieties of potatoes of foreign selection (Newton, Sunshine and Brook) were affected by all 4 aggressive pathogens of the pathogen. Conclusions. Potato varieties that have not been affected by the pathogens of the wart pathogen have been proposed for inclusion in the State Register of Plant Varieties Suitable for Distribution in Ukraine for Introduction in Outbreaks and also breeders to use for crossing disease sources and receiving potato resistant descendents to disease.